Improving Students Learning Outcomes and Digital Literacy on Acid-Base Titration Using Titration Screen Experiment Media - Sri Mulyani; Rakhma Amalia Nurdina; Lina Mahardiani (International Journal of Pedagogy and Teacher Education, 2023)
This study aims to enhance students' digital literacy and learning outcomes in acid-base titration through Titration Screen Experiment Media. The research used a quasi-experimental method with two class samples, including the experimental class utilizing Titration Screen Experiment Media and the control class without it. Data were collected through digital literacy questionnaires and post-test questions evaluating students’ cognitive domain knowledge in acid-base titration. The Multivariate Analysis of Variance (MANOVA) test was used to analyze the data. The results demonstrated that the experimental class, which utilized the Titration Screen Experiment Media, exhibited higher digital literacy levels than the control class and improved learning outcomes in acid-base titration. The average digital literacy score in the experimental class was 56.50, whereas the control class scored 41.70. The experimental class indicated students with intermediate cognitive domain learning outcomes around 84.00, while the control class scored 76.67. These findings suggest that implementing the Titration Screen Experiment Media enhances digital literacy and positively impacts students’ learning outcomes in acid-base titration. Educators can effectively improve students' digital literacy skills by integrating this innovative media into teaching and learning while encouraging their academic achievements in chemistry learning. The research emphasizes the significance of digital literacy in modern education. The practical implication lies in the roles of educators in preparing students’ chemistry digital literacy.